The Constitutional Principles in the Procedure for the Granting of Subsidies in Spain - Villanueva Turnes, Alejandro (Estado, Gobierno y Gestión Pública, 2018)
This study tries to analyse which is the role of the constitutional principles of public grant award procedures in Spain. To do this we will give a concept of the public grant, a brief explanation of different concession procedures, for finally it analyse the principles established by the Law.